Особенности информационных структур предприятий - Пенькова, И.В.; Шарипов, З.Ф. (Культура народов Причерноморья, 2014)
В статье авторы рассматривают аспекты формирования и развития информационных
структур предприятия. При этом исследуется взаимодействие информационной структуры
предприятия и направленности хозяйственно-экономической деятельности предприятия с точки зрения
поиска и отбора необходимой информации. У статті автори розглядають аспекти формування та розвинення інформаційних структур
підприємства. При цьому досліджується взаємний вплив інформаційної структури підприємства і
спрямованості господарчо-економічної діяльності підприємства з точки зору пошуку та вибору
необхідної інформації. In the article authors examine the aspects of formation and development of enterprise informational
structures. Herewith there has been investigated the interaction of an enterprise informational structure and
orientation of enterprise economic activity with relation to the search and selection of necessary information.
The analysis of information collection and its systematization proved that from the great number of existent
principles of information classification enterprises use general methodologies and systems that can be
standardized with the purpose of expenses reduce paid for information search and its systematization.
Development of information and telecommunication technologies facilitated the search process and availability
of information. But it did not take off the problem of processing and systematization of basic data as it requires a
certain goal. Nevertheless, existing methods and systems can be perspective in case of additional revision
relatively specific task;
An informational structure is a determinative of successful and effective enterprise activity, because it reduces
transactional costs, increases an income and enhance the standard of corporate culture